2018
DOI: 10.3329/bjms.v17i4.38321
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Stroke Caregivers: Evidence from a Qualitative Study in Sarawak, Malaysia

Abstract: Background: Stroke survivors experience long-term physical, psychosocial and cognitive impairment that are formidable challenges to caregivers because caring for stroke survivors needs explicit knowledge and caregivers have to endure the stressfulness as a result of caring. In addition, little is known about perceived benefits of the stroke care giving experience.Objectives: This study was aimed to determine the caregivers’ burden and challenges as reported by caregivers of stroke survivors.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Young people are commonly associated with active social life, various wants and needs, the uncertainty of life direction, and the unemployed. Several studies have shown that commitment while caring for stroke patients results in a lack of leisure time with friends and an inability to attend events [ 40 ]. Similar to the theme of life alterations by Wagachchige et al [ 44 ], the family caregivers lacked leisure time and commonly missed attending social gatherings because the stroke patients could not be left alone to manage themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young people are commonly associated with active social life, various wants and needs, the uncertainty of life direction, and the unemployed. Several studies have shown that commitment while caring for stroke patients results in a lack of leisure time with friends and an inability to attend events [ 40 ]. Similar to the theme of life alterations by Wagachchige et al [ 44 ], the family caregivers lacked leisure time and commonly missed attending social gatherings because the stroke patients could not be left alone to manage themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening social support was found to reduce caregiver burden, anxiety, and depression levels in a statistically significant way [ 47 , 48 ]. According to a local study, employed stroke caregivers had difficulty completing their jobs well and performing caregiving chores, which hampered their work performance [ 40 ]. Thus, the formal obligation responsibilities subtheme emergence represented the overburdened employed caregivers with additional work demands during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from a qualitative study in Sarawak, Malaysia (Rahman et al, 2018) Caregivers burden is exacerbated by financial problems, multiple responsibilities, behavioral changes in stroke survivors, and lack of social support. 17 Caregiver burden among caregivers of individuals with severe mental illness: Testing the moderation and mediation models of resilience (Mulud & McCarthy , 2017) Female caregivers felt more burdened.…”
mentioning
confidence: 99%
“…Electrical current is applied through electrodes to one or more targeted muscles. 12-15, 18 The muscle size, the position of the electrodes, and the amount of intervening tissue between muscle and skin dictate the intensity needed from the electrical stimulation unit to cause a contraction. Electrical stimulation therapy was given to this patient in the form of a faradic current.…”
mentioning
confidence: 99%